2023
DOI: 10.1101/2023.06.09.543371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scots pine – panmixia and the elusive signal of genetic adaptation

Abstract: Scots pine (Pinus sylvestris L.) rapidly established dominance across Eurasia after the last ice age. Within this vast region, Scots pine shows remarkable ecological breadth and occurs in environments ranging from temperate rainforests to arid tundra margins. Such expansive distributions can be favored by different demographic and selective processes and the potential feedback between these forces. In this study, we conducted range-wide population genetic analyses and found a high and uniform genetic diversity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Meanwhile, the species’ primary distribution underwent a transition from southern to northern latitudes in tandem with the shifts in glaciation cycles. The recurrent utilization of the same discrete and well-defined refugia across ice-cycles may, at least partially, explain the difference observed between Norway spruce and two other boreal tree species - Pinus sylvestris (Scots pine) and Betula pendula (Silver birch) – both of which display notably less population structure (Bruxaux et al, 2023; Milesi et al, 2023; Tsuda et al, 2017). The latter may have instead survived the glacial periods in a large metapopulation south of the glaciated regions (Hewitt, 2000; Palmé et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the species’ primary distribution underwent a transition from southern to northern latitudes in tandem with the shifts in glaciation cycles. The recurrent utilization of the same discrete and well-defined refugia across ice-cycles may, at least partially, explain the difference observed between Norway spruce and two other boreal tree species - Pinus sylvestris (Scots pine) and Betula pendula (Silver birch) – both of which display notably less population structure (Bruxaux et al, 2023; Milesi et al, 2023; Tsuda et al, 2017). The latter may have instead survived the glacial periods in a large metapopulation south of the glaciated regions (Hewitt, 2000; Palmé et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For P. abies , populations were even extirpated during the LGM from what represents today the niche centroid. Additionally, the long generation time and long-range pollen dispersal of coniferous species could also contribute to the lack of fit to the Niche centrality expectations in these species, as is observed in P. sylvestris across its whole distribution range (Bruxaux et al 2023). Our findings align with recent research that observed minimal variation in estimates of genetic diversity among populations from various dominant forest tree species in Western Europe (James et al, 2023; Milesi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the species' primary distribution underwent a transition from southern to northern latitudes in tandem with the shifts in glaciation cycles. The recurrent utilization of the same discrete and well‐defined refugia across ice cycles may, at least partially, explain the difference observed between Norway spruce and two other boreal tree species— Pinus sylvestris (Scots pine) and Betula pendula (Silver birch)—both of which display notably less population structure (Bruxaux et al., 2023; Milesi et al., 2023; Tsuda et al., 2017). The latter may have instead survived the glacial periods in a large metapopulation south of the glaciated regions (Hewitt, 2000; Palmé et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For P. abies , populations were even extirpated during the LGM from what represents today the niche centroid. Additionally, the long generation time and long‐range pollen dispersal of coniferous species could also contribute to the lack of fit to the Niche centrality expectations in these species, as is observed in Pinus sylvestris across its whole distribution range (Bruxaux et al., 2023). Our findings align with recent research that observed minimal variation in estimates of genetic diversity among populations from various dominant forest tree species in Western Europe (James et al., 2023; Milesi et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, understanding how the genetic diversity of a species is influenced by historical, geographical, and environmental factors requires largescale sampling that encompasses a representative range of environmental conditions encountered by a species. In an article published in this issue of New Phytologist, Bruxaux et al (2024; 1231-1246 sampled Scots pine (Pinus sylvestris L.) across Eurasia and performed genotype by sequencing (GBS) of 2321 individual trees, along with detailed statistical analyses, to determine how its genetic diversity is influenced by geography, ecological conditions, demographic history, and local adaptation.…”
mentioning
confidence: 99%